Synthesis of a PET tau tracer [11C]PBB3 for imaging of Alzheimer’s disease - Wang, Min; Gao, Mingzhang; Xu, Zhidong; Zheng, Qi-Huang (Bioorganic & medicinal chemistry letters, 2015)
[Display omitted] The authentic standard PBB3 and its precursor N-desmethyl-PBB3 as well as TBS-protected N-desmethyl-PBB3 precursor for radiolabeling were synthesized from 5-bromo-2-nitropyridine, acrolein diethyl acetal, 6-methoxy-2-methylbenzothiazole, and diethylchlorophosphate with overall chemical yield 1% in six steps, 2% in five steps, and 1% in six steps, respectively. [11C]PBB3 was prepared from either desmethyl-PBB3 or TBS-protected desmethyl-PBB3 with [11C]CH3OTf through N-[11C]methylation and isolated by HPLC combined with SPE in 20–25% and 15–20% radiochemical yield, respectively, based on [11C]CO2 and decay corrected to end of bombardment (EOB). The radiochemical purity was >99%, and the specific activity at EOB was 370–1110GBq/μmol with a total synthesis time of ∼40-min from EOB.